Desing Thinking-Based Strategies for Entrepreneurial Innovation: A Case Study of University Students in Lima, Peru - Olórtegui Alcalde, Luis Miguel; Saldaña Narro, Julio Brayan; Marcelo Quispe, Luis Alberto; Gasparrini Cañas, Víctor Gerardo (LACCEI, 2025)
This study analyzes the impact of Design Thinking on the development of entrepreneurial competencies among university students in Lima, Peru. Using a quantitative approach based on structural equation modeling (CB-SEM) and a non-experimental design, the study evaluated 385 students with active entrepreneurial experience. The findings reveal that Design Thinking significantly influences creativity (β = 0.62, p < 0.001) and problem-solving (β = 0.55, p < 0.01), highlighting its ability to foster an iterative and sustainable entrepreneurial approach. Barriers such as lack of practical knowledge (41%), time constraints (33%), and limited access to technological resources (26%) were also identified, limiting its effective implementation. The study emphasizes the need for specific educational strategies, such as innovation laboratories and interdisciplinary programs, to address these challenges. Policy implications include promoting alliances between universities, governments, and companies to ensure resources and training in advanced methodologies. Despite the challenges, Design Thinking has proven to be a transformative tool that enhances sustainability and innovation in university-based entrepreneurship. This work contributes not only to the theoretical development of the field but also offers practical recommendations to strengthen entrepreneurial ecosystems in emerging contexts. In conclusion, Design Thinking can catalyze significant progress towards more sustainable and inclusive entrepreneurship, provided that identified barriers are addressed through collaborative and strategic approaches.